Peptide Vaccines for Leishmaniasis - De Brito, Rory C. F.; Cardoso, Jamille M. De O.; Reis, Levi E. S.; Vieira, Joao F.; Mathias, Fernando A. S.; Roatt, Bruno M.; Aguiar-Soares, Rodrigo Dian D. O.; Ruiz, Jeronimo C.; Resende, Daniela de M.; Reis, Alexandre B. (Frontiers in Immunology, 2018)
Due to an increase in the incidence of leishmaniases worldwide, the development of new strategies such as prophylactic vaccines to prevent infection and decrease the disease have become a high priority. Classic vaccines against leishmaniases were based on live or attenuated parasites or their subunits. Nevertheless, the use of whole parasite or their subunits for vaccine production has numerous disadvantages. Therefore, the use of Leishmania peptides to design more specific vaccines against leishmaniases seems promising. Moreover, peptides have several benefits in comparison to other kinds of antigens, for instance, good stability, absence of potentially damaging materials, antigen low complexity, and low-cost to scale up. In contrast, peptides are poor immunogenic alone and they need to be delivered correctly. In this context, several approaches described in this review are useful to solve these drawbacks. Approaches, such as, peptides in combination with potent adjuvants, cellular vaccinations, adenovirus, polyepitopes or DNA vaccines have been used to develop peptide-based vaccines. Recent advancements in peptide vaccine design, chimeric or polypeptide vaccines and nanovaccines based on particles attached or formulated with antigenic components or peptides have been increasingly employed to drive a specific immune response. In this review, we briefly summarize the old, current and future stands on peptide-based vaccines, describing the disadvantages and benefits associated with them. We also propose possible approaches to overcome the related weaknesses of synthetic vaccines and suggest future guidelines for their development.